2011
DOI: 10.1104/pp.110.169821
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Sinapine Esterase BnSCE3 in Oilseed Rape Seeds Triggers Global Changes in Seed Metabolism    

Abstract: Sinapine (O-sinapoylcholine) is the predominant phenolic compound in a complex group of sinapate esters in seeds of oilseed rape (Brassica napus). Sinapine has antinutritive activity and prevents the use of seed protein for food and feed. A strategy was developed to lower its content in seeds by expressing an enzyme that hydrolyzes sinapine in developing rape seeds. During early stages of seedling development, a sinapine esterase (BnSCE3) hydrolyzes sinapine, releasing choline and sinapate. A portion of cholin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 59 publications
(58 reference statements)
0
45
0
Order By: Relevance
“…Moreover, Kim et al (2015) reported that the level of indole-3-acetaldoxime, a precursor in indole GLS, auxin, and camalexin biosynthesis, negatively affected SM level in Arabidopsis. Based on available information on the SM biosynthetic pathway (Clauss et al, 2011) and our results, we speculate that SM biosynthesis is regulated through a novel molecular mechanism that may involve reactive oxygen species. Future studies using an integrative analysis of transcriptomics and metabolomics are required to identify the regulatory network of SM biosynthesis from signaling to metabolite biosynthesis.…”
Section: Aphid-induced Plant Resistancementioning
confidence: 51%
“…Moreover, Kim et al (2015) reported that the level of indole-3-acetaldoxime, a precursor in indole GLS, auxin, and camalexin biosynthesis, negatively affected SM level in Arabidopsis. Based on available information on the SM biosynthetic pathway (Clauss et al, 2011) and our results, we speculate that SM biosynthesis is regulated through a novel molecular mechanism that may involve reactive oxygen species. Future studies using an integrative analysis of transcriptomics and metabolomics are required to identify the regulatory network of SM biosynthesis from signaling to metabolite biosynthesis.…”
Section: Aphid-induced Plant Resistancementioning
confidence: 51%
“…BnSCE3-overexpressing seeds were nearly devoid of sinapine. However, in contrast to the silencing of BnREF1 and UGT84A9, the fraction of related sinapate esters was not affected by the induced sinapine esterase activity (Clauss et al, 2011). With regard to conventional breeding, BnREF1 genes appear as the favored molecular targets.…”
Section: Metabolic Redirection Triggered By Bnref1 Suppressionmentioning
confidence: 91%
“…On the other hand, an increase was observed in the amounts of nonacylated kaempferol 3-O-sophoroside (42) and its sinapoylated derivative (43). The overaccumulation of compounds 42 and 43 was also found in the oilseed rape transformant suppressing UDP-Glc:sinapate glucosyltransferase (UGT84A9), the enzyme converting sinapate to 1-O-sinapoylglucose (Wolfram et al, 2010) and in the transgenic overexpressor of sinapoylcholine esterase (BnSCE3) involved in sinapine hydrolysis (Clauss et al, 2011). Hence, this metabolic change should be related to a perturbed sinapate ester metabolism.…”
Section: Metabolic Redirection Triggered By Bnref1 Suppressionmentioning
confidence: 99%
See 2 more Smart Citations